Physicochemical Characters of Mosquitoes Natural Breeding Habitats: First Record in High Dengue Hemorrhagic Fever Cases Area, East Java, Indonesia - Rosmanida Rosmanida; Shifa Fauziyah; Adi Pranoto Pranoto (Universitas Gadjah Mada, 2020)
This research aims to identify physicochemical characteristics in natural breeding habitats/ phytotelmata of dengue vector—including Aedes (Stegomyia) aegypti and Aedes (Stegomyia) albopictus. The research was conducted during rainy season and pre-dry season (from January to June 2017) in the region with the high cases of Dengue Hemorrhagic Fever (DHF). The entomological survey was carried out by stratified random sampling in urban and rural areas in order to find potential breeding habitats, every natural breeding habitats in sampling location were checked for the presence of Aedes larvae. Physicochemical characters that consist of temperature, turbidity, carbon dioxide, ammonia, nitrate, sulphate, pH and dissolved oxygen were recorded. Larval species were taken and then identifying activities were conducted in the Laboratory of Entomology. Data were analysed using the Chi-square test. Results showed that only dissolved oxygen that significantly associated with larval abundance (p=0.039). while others are not significantly associated. Whereas, other characters are associated with each other, carbon dioxide associated with the ammonia and sulphate (p=0.001; p=0.028). Turbidity associated with the dissolved oxygen (p=0.022) and pH associated with nitrate (p=0.001).